Nanomaterials-based electrochemical and optical biosensors for food safety regulations and point-of-care diagnosis - Ang, Wei Li (Nanyang Technological University, 2022)
With the ever-present demand for the development of rapid, sensitive, selective and cost-effective biosensors, two-dimensional (2D) nanomaterials-based biosensors have achieved great success in the recent years owing to the excellent properties nanomaterials possess. Particularly, graphene and its derivatives have been extensively utilized for the pursuit of electrochemical and optical biosensors to offer cost-effective alternatives to the current costly instrumental methods. In fact, graphene oxides, the oxidized form of graphenes, have been utilized as electroactive labels or platforms owing to the good conductivity, large surface area and fast heterogeneous electron transfer (HET) rates they offer. Moreover, Graphene Quantum Dots (GQDs), a zero-dimensional graphene oxide derivative, have also been successfully employed for optical applications, particularly in the development of optical biosensors. Down the periodic table for Group XIV elements, the search for other carbon-based nanomaterials as an alternative to graphene have been omnipresent owing to the great success graphene have displayed over the years. Specifically, germanium, a group XIV element, have recently gained increasing interests among many researchers. Therefore, this work highlights and demonstrates the suitability of nanomaterials for the rapid and cost-effective detection of biological analytes under optimized conditions for the purpose of food safety and point-of-care diagnostics applications.